Herpes Simplex Virus Mistyping due to HSV-1 × HSV-2 Interspecies Recombination in Viral Gene Encoding Glycoprotein B - Casto, Amanda M. (Viruses, 2020)
Human herpes simplex viruses (HSV) 1 and 2 are extremely common human pathogens with overlapping disease spectra. Infections due to HSV-1 and HSV-2 are distinguished in clinical settings using sequence-based “typing” assays. Here we describe a case of HSV mistyping caused by a previously undescribed HSV-1 × HSV-2 recombination event in UL27, the HSV gene that encodes glycoprotein B. This is the first documented case of HSV mistyping caused by an HSV-1 × HSV-2 recombination event and the first description of an HSV interspecies recombination event in UL27, which is frequently used as a target for diagnostics and experimental therapeutics. We also review the primer and probe target sequences for a commonly used HSV typing assay from nearly 700 HSV-1 and HSV-2 samples and find that about 4% of HSV-1 samples have a single nucleotide change in at least one of these loci, which could impact assay performance. Our findings illustrate how knowledge of naturally occurring genomic variation in HSV-1 and HSV-2 is essential for the design and interpretation of molecular diagnostics for these viruses.